INVESTIGATION OF CRITICAL PARAMETERS AFFECTING ASPHALTENES PRECIPITATION DURING C02 INJECTION IN MALAYSIAN OILFIELD - W RAZAK, WAN NURUL ADYANI (2012)
The study was conducted to investigate the fundamental aspects of asphaltene precipitation during CO2 flooding in EOR applications. The oil samples used in this study are from peninsular Malaysia oilfield (PMO) and Sarawak oilfield (SKO). Asphaltenes precipitation during CO2 injection for EOR applications in Malaysian oilfield was evaluated using Near-Infra-Red Solids-Detection-System (NIR-SDS). Five different samples from Malaysian oilfield were investigated in this study i.e. four bottomhole samples and one recombined sample. Variation in pressure, temperature and composition were thoroughly investigated to monitor their impact on CO2 induced asphaltenes precipitation tendency. Only two out of five samples shows tendency to develop asphaltenes precipitation problem during CO2 injection study. Variation in temperature shows no influence on asphaltene precipitation if the asphaltenes problem does not occur during pressure changes. (Only cover Reservoir Temperature and Wellhead Temperature). Physiochemical properties of the two samples were compared against the nonproblematic samples. It was found that crude oil that has high GOR, high API and low molecular weight have higher propensity to create asphaltene precipitation problem during CO2 injection. Percentage of asphaltenes deposited and precipitated from depressurization test was recorded by HPHT filtration technique. Results show that most of solids asphaltenes in this case are in precipitation form and the deposited asphaltenes on PVT cell wall are a very small amount. Precipitated asphaltenes samples were then characterized by FTIR and NMR spectroscopy. The spectroscopic analysis found that the solids were mainly wax, while asphaltenes could be in a very small amount and was not detected by thesespectroscopy techniques. Asphaltene modeling was then conducted on five samples using AEOS (Association Equation of State) as underlying theory in the modeling tool named as DBR Solids software. Asphaltene precipitation modeling by this technique required tuning of binary interaction parameter and asphaltene molar volume. Comparison from asphaltene model and experimental works produce a similar result.